Драгоценности Рюриковичей по письменным памятникам (столовая посуда и приборы) - Hrynkiewicz-Adamskich, Bożena (Studia Rossica Posnaniensia, 2019)
The aim of the article is to present the names of the valuables in testaments of the Russian great and appanage princes of the 14–16 c. Special attention has been paid to tableware terminology. Lexicographical and etymological data as well as the semantic classification of the tableware names are provided. Dishes and eating utensils used by the Rurik dynasty members during feasts were made of gold or silver and were extremely decorative. According to Thorstein Veblen, conspicuous consumption and wasteful expenditure were signs of person’s high social position. The author draws our attention to the fact that vicarious consumption on the house by invited guests was possible too. Therefore, the social meaning of these valuables is presented in this article.